1998
DOI: 10.6028/nist.ir.6244
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of R123 pool boiling by addition of hydrocarbons

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…The decrease of surface tension causes the decrease of the superheat degree of the bubble nucleation, the decrease of bubble departure diameter, and the increase of bubble departure frequency. (2) The surfactants accumulate at the heating surface and form the excess layer, reducing the surface-energy between the liquid and the heating surface [13], thus the active nucleation sites increase. (3) The surfactants may aggregate in the fluid and form the large particles [28].…”
Section: Effects Of Surfactant On the Nucleate Pool Boiling Heat Tranmentioning
confidence: 99%
See 2 more Smart Citations
“…The decrease of surface tension causes the decrease of the superheat degree of the bubble nucleation, the decrease of bubble departure diameter, and the increase of bubble departure frequency. (2) The surfactants accumulate at the heating surface and form the excess layer, reducing the surface-energy between the liquid and the heating surface [13], thus the active nucleation sites increase. (3) The surfactants may aggregate in the fluid and form the large particles [28].…”
Section: Effects Of Surfactant On the Nucleate Pool Boiling Heat Tranmentioning
confidence: 99%
“…For the effect of surfactant on the nucleate pool boiling heat transfer of pure water, organic fluids or water-organic fluid mixtures, most of the researches indicated that the presence of surfactant enhances the nucleate pool boiling heat transfer [6][7][8][9][10][11][13][14][15], but some researches indicated that the surfactant deteriorates the nucleate pool boiling heat transfer or has little effect on the nucleate pool boiling heat transfer [5,12]. For the effect of surfactant on the nucleate pool boiling heat transfer of water-based nanofluid, the research reported by Chopkar et al [16] showed that the presence of surfactant deteriorates the nucleate pool boiling heat transfer, but the research reported by Kathiravan et al [17] showed that the presence of surfactant enhances the nucleate pool boiling heat transfer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, rather than using the boundary conditions to solve for the interior temperatures, the interior temperatures were used to solve for the boundary conditions following a backward stepwise procedure given in Kedzierski (1995 Kedzierski (1998) Figure 9 shows that the heat transfer coefficient increases with decreasing AT S due to decreasing condensate film thickness with decreasing AT S , As expected, most of the heat transfer coefficients for the R 123/isopentane mixture are less than that of pure R123. The heat transfer coefficients for R 123/isopentane (99.5/0.5) for AT S < 1 are significantly less than that of pure R123.…”
Section: Introductionmentioning
confidence: 86%
“…However, the economic benefit of additives that enhance boiling heat transfer can be realized only when the additive does not significantly degrade the condensation heat transfer. Kedzierski (1999) In another boiling additive study, Kedzierski (1998) Kedzierski and Worthington (1993), the size and arrangement of the thermocouple wells were designed to minimize the errors in the wall temperature and temperature gradient measurement.…”
Section: Introductionmentioning
confidence: 99%